UNSUR BIROKRASI KEMASYARAKATAN DESA SUKAWANA PADA MASA BALI KUNO: KAJIAN BERDASARKAN DATA PRASASTI SUKAWANA D - Wirtawan, I Wayan (Humanis; Volume 5. No. 1. Oktober 2013, 2013)
The Sukawana D epigraphy is one of culture inheritance as the remnant of ancients in Sukawana Village, Kintamani Sub-district, Bangli Regency. The Sukawana D epigraphy was issued by a rulling governor king at the Ancient Bali time named Raja Patih Kbo Parud on 1222 saka (1300 AD). Raja Patih Kbo Parud was a ruler who came from Singasari kingdom, when King Kertanagara made expansion to Bali. This research has purpose to answer the main problems that have been proposed those are about bureaucracy element, and the continuity of the bureaucracy element to Sukawana Village based on data of Sukawana D epigraphy. This research is carried out by using some data collection methods such as observation, literature study, and interview, and data processing method through some analysis such as the non-physical analysis and contextual analysis. Theories that are used in this research are the structural functionalism theory and the bureaucracy theory. Based on the analysis result, it is found out that the bureaucracy element obtained from this research that are according to the content of the Sukawana D epigraphy is as the following. The bureaucracy structure of the central level consists of the king (Raja Patih Kbo Parud), the senapatis, the samgats, and the clergymen of Siwa and Buddha. Whereas the bureaucracy structure in area level are the kab?yans that consist of Kab?yan Arg?, Kab?yan Tuha, Kab?yan T?a?, and Kab?yan Ñoman. Based on the description above the existence of continuity of bureaucracy element in area level that is still going on in the present time in Sukawana Village is the kab?yan.
Keywords: Epigraphy, Bureaucracy Element, Continuity